Capacidade antioxidante in vitro e efeito hepatoprotetor de umbu (Spondias Tuberosa Arr. Cam.) em resposta ao estresse oxidativo induzido por tetracloreto de carbono - Nonato, Edilene Fernandes (2017)
The umbu (Spondias tuberosa Arr. Cam) has importance in the sustainability of extractive activities and of the commercial viability of these products in the Brazilian Northeast. It plays an important socioeconomic role and provides many job opportunities for many farmer's families. The umbu is consumed either in natura or its pulp and it is used to prepare beverages, jams or ice-cream. The study aimed to assess in vitro and in vivo antioxidant and hepatoprotective activities of umbu against oxidative stress induced by carbon tetrachloride (CCl4). Initially, the centesimal composition, pH, total soluble solids (TSS), total titratable acidity (TTA) and TSS/TTA ratio were determined. The antioxidant activity was evaluated in vitro in aqueous extracts (EAq), hydroethanolic (EtOH) and hydromethanolic (MetOH) extracts using the DPPH, ABTS and FRAP assays, while the hepatoprotective properties of EAq were investigated on oxidative stress induced by CCl4 in Wistar rats, using two doses of extract (200 and 400 mg/kg b.w.), administered orally, for 14 days. The pulp of umbu contains high amount of water and reduced caloric value. It had low pH value and considered acidic fruit. On the other hand, the SST and AAT parameters found were 9.67 +- 0.06 (ºBrix) and 1.75 +- 0.02 (mg/100 g citric acid), and SST/AAT ratio (5.53) was between intermediate values for the fruit at 2 (onset of enhanced levels of pigmentation) and 3 (predominant yellow coloration) ripening stages, whose it refers to the most preferred to consumption by the population.The extracts exhibited a strong in vitro antioxidant activity, (55 - 86%) scavenging DPPH and 663,6 ( +- 31.0) to 1,902.0 ( +- 9.4) de mol Trolox. g-1 ABTS radicals in a dosedependent manner and FRAP of extract was expressive, although, it does not present similar activity when compared to the Trolox standard.The treatment with EAq (200 mg/kg b.w.) showed the hepatoproctetive activity was confirmed with significant decrease of the serum markers of the live damage, both aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels by 36.26% and 48.57%, respectively as compared to the CCl4 treated group. Antioxidant capacity of liver tissue determined using FRAP assay was maintained when as compared to the CCl4 treated group. Thus, the antioxidant reduced capacity of hepatic tissue CCl4 treated group probably is correlated to the depletion of the animal endogenous antioxidant system. Oxidative stress was reduced by lowering of thiobarbituric acid reactive substances approximately 92% and 52% by extracts (200 and 400 mg/kg b.w.), respectively. Therefore, it is suggested umbu pulp presents as a natural source of antioxidants, with hepatoprotective effect against CCl4-induced toxicity.